Perioperative management for elderly patients undergoing day surgery: evidence-based practice for nursing care and day surgery - Wu, Mei; Xia, Lu; Zhang, Li; Xu, Yamin; Cheng, Yun; Zhang, Xiaoju; Chen, Long (Frontiers in Medicine, 2023)
Introduction: It is necessary to explore the evidence-based practice of perioperative management of elderly patients undergoing ambulatory surgery, to optimize the clinical work flow and improve the quality of nursing care. Methods: Based on the best evidence obtained from the previous study, the perioperative management model and examination index of elderly patients undergoing day surgery were established, and the evidence of best practice was obtained by using evidence-based methodology. Then we integrated evidence into clinical practice and improved the process. We made a comparative analysis of the effect before and after the implementation of the evidence. Results: This study summarized 26 pieces of evidence of perioperative management of elderly patients undergoing day surgery, and transformed the evidence into 7 items and 11 items of examination index. After the application of the best evidence, nurses' knowledge, belief and practice of perioperative management of elderly patients in day operation ward reached 100%, and the rate of reaching the standard of most indicators increased after the application of evidence. The length of waiting for admission, waiting for operation and returning to the ward to discharge of elderly patients all decreased significantly, and the difference was statistically significant (All p < 0.05). Conclusion: Evidence-based perioperative management of elderly patients undergoing day surgery improves the nursing practice of clinical nurses, shorten the waiting time and hospitalization time of elderly patients undergoing day surgery, which should be promoted in clinical nursing care.